Analisis Yuridis Penetapan Nomor 916/Pdt.P/2022/PN.Sby Terkait Kasus Pernikahan Beda Agama Ditinjau Berdasarkan Hukum Islam dan Undang-Undang Nomor 1 Tahun 1974 tentang Perkawinan - Alex Sugandi (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
In Indonesia, interfaith marriages have not been clearly regulated in the law. This phenomenon makes it a reality that the Indonesian nation consists of various religions. The heterogeneity of the Indonesian people makes it possible for even religious marriages to occur. The problem in this thesis is that the author found a case related to Interfaith Marriage, namely the determination of the Judge at the Surabaya District Court who granted the request for interfaith marriage between Rizal Adikara, a Muslim couple and Eka Debora Sidauruk, who was a Christian through the stipulation Number 916/Pdt.P/2022/ PN.Sby. This type of research is normative legal research, the research method is carried out by examining library materials that are related to the issues raised, namely the determination of the Surabaya District Court on the application of interfaith marriage. qualitative analysis is then carried out. This study aims to determine the legality of interfaith marriages based on Marriage Law Number 1 of 1974 and Islamic Law and to determine the basis of judges' considerations in granting requests for interfaith marriage determinations through analysis of the judge's decision in the form of stipulation. From this study it can be concluded that, firstly whether or not interfaith marriages are carried out according to existing religions in Indonesia, it all depends on the legal rules of each governing religion. Because in principle the five religions in Indonesia strongly oppose the existence of interfaith marriages, secondly the judge's legal considerations in the decision number 916/Pdt.P/2022/PN.Sby. Interfaith marriage refers to Law Number 1 of 1974 concerning Marriage, that in that law there is no single article that stipulates that interfaith marriage is prohibited in Indonesia. Keywords: Marriage, Different Religion, Judge's Consideratio